ANALISIS SWOT STRATEGI PEMERINTAH DAERAH KABUPATEN BANDUNG DALAM PENANGANAN KONFLIK HORIZONTAL ORGANISASI MASYARAKAT DI KABUPATEN BANDUNG - Rendy Adiwilaga; mustofa, Mustabsyirotul Ummah Mustofa; Kansah Eka Permana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
Mass or Community Organizations (Ormas) in principle represent an established and healthy democratic life, because the existence of mass organizations is included in the category of freedom of association and assembly for the community. Unfortunately, many Civil Society Organizations (CSOs) are involved in conflicts of interest which lead to open violence, including the Bandung Regency which has a fairly high productivity of CSO establishments. This study uses a SWOT analysis which contains the variables of strengths, weaknesses, opportunities and threats, and a qualitative method with a case study approach. The results of the study show that from the aspect of strength, the local government is represented by Kesbangpol as a work unit that has direct contact with Ormas, the first of which is support from "sides" in coaching, namely the TNI and POLRI. There is full control over the distribution of grant funds from the Government of Bandung Regency. Meanwhile, the weaknesses are the minimum number and quality of human resources who intensely accompany CSOs resulting in a lack of oversight, and many CSO leaders do not know the function of Kesbangpol. In fact, in terms of opportunities, the community has intensively used social media so they can carry out surveillance at any time, plus every mass organization has strong militancy, which is useful in terms of program mobilization if the mass organization knows about Kesbangpol's existence. With regard to threats, it is possible for mass organizations to not consider the existence of the Kesbangpol and Regional Government so that conflict escalations between mass organizations are increasing